Development of autonomous electromagnetic two speed gearbox for electric vehicle - Hasan, Md Nurul (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
The goal of the National Automotive Policy (NAP) 2020 is to develop advanced automotive technologies for the next generation vehicle (NxGVs) with improving energy efficiency and autonomous for the future mobility in Malaysia. Conventional transmissions such as automatic transmission (AT), manual transmission (MT), and / or continuously variable transmission (CVT) for NxGV will cause energy consumption due to their bulkiness and difficulty to install directly with the EV's motor-head. In addition, the single-speed gearbox (SS-GB) is lighter, but not suitable for generating enough torque at start-up or when going uphill. Therefore, the development of a compact and autonomous energy-efficient transmission is a key technological issue for NxGV. The aim of this study is to fabricate a prototype of a compact and lightweight autonomous electromagnetic two-speed gearbox (AEM2SGB) for EV in accordance with NAP-2020 and IR4.0. The first-gear is used for acceleration in uphill, which provide high torque, and the second-gear is used for higher speed. A compact and lightweight laboratory-scale AEM2SGB has been developed. Furthermore, an autonomous fuzzy controlled system has been developed with associating the wheel speed sensor and motor sensor to control the power flow to the electromagnetic actuator (EMA). A laboratory experiment is conducted using equivalent road-loads. It is observed that the AEM2SGB's shift times in first gear to be 1.5 seconds with a higher torque of 3000 Nm and 1.8 seconds in second gear for 110 km / h with supplying current in the range of 12-16A. Keywords: Electromagnetic gearbox; Fuzzy logic controller; Energy efficient; Gear shifting time.